Differences between Breast Conservation‐Eligible Patients and Unilateral Mastectomy Patients in Choosing Contralateral Prophylactic Mastectomies. Issue 6 (26th August 2016) - Sabel, Michael S.; Kraft, Casey T.; Griffith, Kent A.; Bensenhaver, Jessica M.; Newman, Lisa A.; Hawley, Sarah T.; Momoh, Adeyiza O.
Abstract: There has been an increasing use of bilateral mastectomy (BM) for breast cancer. We sought to examine our trends among breast conservation (BCT) candidates and women recommended for unilateral mastectomy (UM). Our prospective breast cancer database was queried for women with a first‐time, unilateral breast cancer. Patient and histologic factors and surgical treatment, including reconstruction, were evaluated. A detailed chart review was performed among patients from two representative time periods as to the reasons the patient underwent mastectomy. We identified 3, 892 women between 2000 and 2012 of whom 60% underwent BCT, 1092 (28%) had UM and 12% underwent BM. BM rose from 4% in 2000 to a high of 19% in 2011, increasing around 2002 for women <40. BCT was less likely with decreasing age (p < 0.0001), lobular histology (p < 0.0001), higher stage (p < 0.0001) and decreasing BMI (p < 0.0001). Among mastectomy patients, contralateral mastectomy was associated with decreasing age (p < 0.0001), Caucasian race (p < 0.0001), and lower stage (p = 0.005). Over time, indications for mastectomy decreased while patients deemed BCT‐eligible opting for UM or BM increased dramatically. Increases in the use of BM are in large part among women who were otherwise BCT‐eligible. Factors associated with BM use are different for BCT‐eligible patients and those recommended for UM. A better understanding of the factors driving individual patient choices is needed.